Dental caries prevention strategies among children and adolescents with immigrant - or low socioeconomic backgrounds- do they work? A systematic review - Marit S. Skeie; Kristin S. Klock (BMC, 2018)
Abstract Background This systematic review was designed to uncover the most reliable evidence about the effects of caries preventive strategies in children and adolescents of immigrant or low socioeconomic backgrounds. Methods According to pre-determined inclusion and exclusion criteria, relevant articles focusing on underprivileged groups were electronically selected between January1995 and October 2015. The literature search was conducted in five databases; PubMed, Embase, CINAHL, SweMed+ and Cochrane Library. Accepted languages for included articles were English, German and Scandinavian languages. Abstracts and selected articles in full text were read and assessed independently by two review authors. Systematic reviews and meta-analyses were not included. Also articles with topics of water fluoridation and fluoride toothpaste were excluded, this due to all existing evidence of anti-caries effect for disadvantaged groups. The key data about the main characteristics of the study were compiled in tables and a quality grading was performed. Results Thirty-seven articles were selected for further evaluation. Supervised toothbrushing for 5-year-old school children was found to be an effective prevention technique for use in underprivileged groups. Also a child/mother approach, targeting nutrition and broad oral health education of mothers showed effectiveness. For older children, a slow-release fluoride device and application of acidulated phosphate fluoride (APF) gel showed to be effective. Conclusion On the basis of this review, we maintain that in addition to studies of water fluoridation and fluoride toothpaste, there are other preventive intervention studies providing scientific evidence for caries reduction among children and adolescents with immigrant or low socioeconomic backgrounds.